If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 7 + -4x = 23 Reorder the terms: 7 + 8x + -4x = 23 Combine like terms: 8x + -4x = 4x 7 + 4x = 23 Solving 7 + 4x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4x = 23 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = 23 + -7 4x = 23 + -7 Combine like terms: 23 + -7 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 5(29)+5= | | 8x^3-12x=0 | | 2x^3+17x^2+46x+40= | | 0=n-18-4n | | 20r^2+73r+63=0 | | -0.75p-2=0.25 | | 2x=1.5(x+15) | | 6x^2-42p+60=0 | | 10x+10=10x-2 | | 6x+49=8x-11 | | 3(w+1)+7w=4(w+1)-5 | | 2m+16=4+6m | | 6x+-4+9x+16= | | c^3-9c^2-4c+36=0 | | 2x-5(x-3)=-2+4x-25 | | 4(3z-2)=2(n+1) | | 5(12-2x)=3(7+5x) | | 8=4r+16 | | 7(y-9)+24=3(y-6) | | 13x-20-41=8x | | 6+8b=9b | | -100=-t/3-90 | | 90.47=.6x-54.31 | | x^2-12x+36=45 | | 5.49(43/4)= | | 8y-5(c+2)=7 | | 7r^3-7r=0 | | 24=-2(5-x)+4 | | -7.2q+1.8=-19.8 | | 10s^3-250s=0 | | 3(-9)=30 | | 54.31-.6=90.47 |